Two-Stage Chaotic Colpitts Oscillator for the UHF Range - Mykolaitis, G.; Tamaševičius, A.; Bumelienė, S.; Baziliauskas, A.; Lindberg, E. (Elektronika ir Elektrotechnika, 2004)
A hardware prototype of the novel two-stage Colpitts oscillator employing the microwave BFG520 transistors with the threshold frequency of 9 GHz is described. The circuit is investigated both numerically and experimentally. Typical phase portraits and broadband continuous power spectra demonstrate chaotic performance of the oscillator in the ultrahigh frequency range (UHF: 300 to 1000 MHz). The two-stage chaotic Colpitts oscillator exhibits better spectral characteristics compared to a classical single-stage Colpitts oscillator. The relative bandwidth is 0.47 and 0.74 for the central frequency of about 500 MHz within the spectral unevenness of 10 dB and 20 dB, respectively. Ill. 4, bibl. 5 (in English; summaries in Lithuanian, English, Russian).